2011
DOI: 10.1902/jop.2010.100160
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Oral Mucosal Thickness Measurements Using Spiral Computed Tomography

Abstract: The correlation between spiral CT and physical measurement was high except in sites of very thin mucosa. Spiral CT can be considered an alternative method for the measurement of oral mucosal thickness. Because of the higher radiation exposure, caution should be exercised and radiation dosage versus clinical benefit assessment is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 30 publications
(53 reference statements)
4
45
1
Order By: Relevance
“…Soft tissue thickness has been measured using different methods over the years including periodontal probe, 16 endodontic files, 1,37 spiral CT, 37 and others. Soft tissue CBCT is an accurate, convenient, and painless technique for obtaining a 3-dimensional overview of the soft tissue along with its supporting bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft tissue thickness has been measured using different methods over the years including periodontal probe, 16 endodontic files, 1,37 spiral CT, 37 and others. Soft tissue CBCT is an accurate, convenient, and painless technique for obtaining a 3-dimensional overview of the soft tissue along with its supporting bone.…”
Section: Discussionmentioning
confidence: 99%
“…Soft tissue CBCT is an accurate, convenient, and painless technique for obtaining a 3-dimensional overview of the soft tissue along with its supporting bone. 13,[37][38][39][40] Gingival tissue thickness has been measured at points ranging 1 to 3 mm apical in relation to the bone crest 14 or gingival margin. 1,41 Fu 13 assessed the soft tissue thickness 2 mm apical to the bone crest with a caliper (0.5 mm; range, 0.1-1.2 mm) and compared it with the measurements obtained from the CBCT scans (0.57 mm; range, 0.2-1.86 mm) and found no significant difference among them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Such evaluation is much more important for implant treatment because this treatment passes through both the jawbone and oral mucosa or gingiva. A clinical trial has been proposed to evaluate marginal bone by computed tomography scan analysis, 5 but there is a rising need for soft tissue diagnosis.…”
mentioning
confidence: 99%
“…Helical CT has been used to evaluate alterations in paranasal sinuses, including opacification and changes in the sinus walls, due to pathologies including malignant diseases. 7,8 In studies involving the MS, these images are frequently used to define the gold standard. 9 However, according to the studies by Pinsky et al 10 The underlined values represent the accordance observed.…”
Section: Discussionmentioning
confidence: 99%